Glycyrrhizin attenuates renal inflammation in a mouse Con A-hepatitis model via the IL-25/M2 axis - Lingyun Li; Yuanyue Zhang; Zhongyan Wang; Xiangyu Chen; Min Fang (Renal Failure)
Glycyrrhizin (GL) has immunoregulatory effects on various inflammatory diseases including hepatitis and nephritis. However, the mechanisms underlying the anti-inflammatory effect of GL on renal inflammation are not fully understood. Hepatorenal syndrome (HRS) is a functional acute renal impairment that occurs in severe liver disease, and we found that kidney injury also occurs in Con A-induced experimental hepatitis in mice. We previously found that GL can alleviate Con A-induced hepatitis by regulating the expression of IL-25 in the liver. We wanted to investigate whether GL can alleviate Con A-induced nephritis by regulating IL-25. IL-25 regulates inflammation by modulating type 2 immune responses, but the mechanism by which IL-25 affects kidney disease remains unclear. In this study, we found that the administration of GL enhanced the expression of IL-25 in renal tissues; the latter promoted the generation of type 2 macrophages (M2), which inhibited inflammation in the kidney caused by Con A challenge. IL-25 promoted the secretion of the inhibitory cytokine IL-10 by macrophages but inhibited the expression of the inflammatory cytokine IL-1β by macrophages. Moreover, IL-25 downregulated the Con A-mediated expression of Toll-like receptor (TLR) 4 on macrophages. By comparing the roles of TLR2 and TLR4, we found that TLR4 is required for the immunoregulatory effect of IL-25 on macrophages. Our data revealed that GL has anti-inflammatory effects on Con A-induced kidney injury and that the GL/IL-25/M2 axis participates in the anti-inflammatory process. This study suggested that GL is a potential therapeutic for protecting against acute kidney injury.